The CDM-Net Project: The Development, Implementation and Evaluation of a Broadband-Based Network for Managing Chronic Disease. (9th February 2012) - Jones, Kay; Dunning, Trisha; Costa, Beth; Fitzgerald, Kristine; Adaji, Akuh; Chapman, Colin; Piterman, Leon; Paterson, Moira; Schattner, Peter; Catford, John
Abstract : Background . In Australia most chronic disease management is funded by Medicare Australia through General Practitioner Management Plans (GPMPs) and Team Care Arrangements (TCAs). Identified barriers may be reduced effectively using a broadband-based network known as the Chronic Disease Management Service (CDMS). Aims . To measure the uptake and adherence to CDMS, test CDMS, and assess the adherence of health providers and patients to GPMPs and TCAs generated through CDMS. Methods . A single cohort before and after study. Results . GPMPs and TCAs increased. There was no change to prescribed medicines or psychological quality of life. Attendance at allied health professionals increased, but decreased at pharmacies. Overall satisfaction with CDMS was high among GPs, allied health professionals, and patients. Conclusion . This study demonstrates proof of concept, but replication or continuation of the study is desirable to enable the impact of CDMS on diabetes outcomes to be determined.